Spinal cord stimulation in the treatment of neuropathic pain: Current perspectives of indications, cost-effectiveness, complications and results - Bruno Camporeze; Renata Faria Simm; Iracema Araújo Estevão; Luis Roberto Mathias Junior; Paulo Henrique Pires de Aguiar; Sylvine Carrondo-Cottin (Journal of Health Sciences, 2017)
Introduction: The spinal cord stimulation (SCS) has been described as a valuable neuromodulating procedure in the management of chronic and medically untreated neuropathic pain. Although, many studies have discussed the use of this technique, a question still remains regarding its efficacy in different medical conditions with different etiology in the long term. The aim of this paper is to discuss the risks, complications, cost-effectiveness and results of SCS in patients affected by chronic neuropathic pain based on the comprehensive literature review.